MEDICAL CARE AND ENVIRONMENTAL ISSUES AT AVESTO (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Among all social issues, medical issues related to human health play an important role in Avesto. The experience of the medical rules given in the Avesto shows that the countries of the ancient East have such an ancient history as India, China, Iran, Arabia, Egypt and other countries. The Avesta scholar Hamidjon Hamidov writes that the image of a vessel with the venom of a snake, a symbol of medicine, was first depicted in the Avesto. (See: Hamidov H. The fame of "Shohnoma".-T .: "Uzbekistan", 1991, p. 94, the book with the symbol of medicine // "Ishonch", June 30, 2001).According to Avesta scholars, the great Greek scientist Hippocrates (460-377 BC) compiled a text of an oath consisting of ethical-medical rules for practitioners, summarizing unique medical data and experiences. However, it is fair to say that several centuries before the Hippocratic Oath, the Oath of the Physicians was given in the Vandidod section of the Avesto. (See: H. Boboev, T. Dustjanov, S. Hasanov. “Avesto” is a priceless monument of the eastern peoples, p. 57).